Rancang Bagun Aplikasi Mobile Ekatalog Berbasis IOS Sebagai Media Bantu Pengenalan Produk Miulan - Ashari Juang; Desi Purwanti; Etika Kartikadarma (Jurnal Informatika Upgris, 2016)
Abstract Miulan Hijab is a business entity who produces hijab and Muslim clothing for the ladies. Most of the current consumers are those who actively using the social media. The social media such as twitter and Facebook views the products in a timeline (based on the time update) making it difficult to show the well-organized product. However miulanhijab.com website is used as a landing page, or marketing media. But the website does not have an optimum display when opened using an iOS device. Now Miulan hijab businesses is booming, this make Miulan requires an alternative media to develop the brand and the business to a higher segment. This research is a forward engineering research. Forward engineering: life cycle engineering begins from the plan, analysis, and construct, until applied. This research will explain how to develop a mobile application with the iOS platform as a supplementary media for Miulan hijab product introduction. The expected contribution is to provide a design for mobile application developers of iOS-based eCatalog. The details of the development of this application will be reviewed in the report. Keywords: iOS, Miulan Hijab, eCatalog, Mobile Applications.